2005
DOI: 10.1248/jhs.51.357
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Degradation of Disinfectants. A New Chlorhexidine Degradation Intermediate (CHDI), CHDI-C, Produced by Pseudomonas sp. Strain No. A-3

Abstract: C NMR and fast atom bombardment mass spectra studies. Based on the spectroscopic data, this product was assumed to be a modified compound of chlorhexidine (molecular weight, MW; 530). From the proposed structure, CHDI-C was assumed to be a new chlorhexidine degradation intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…Since these peaks were highly comparable with those of the CHX standard, we may further conclude that CHX does not appear to be modified or degraded within D. acidovorans biofilms. CHX degradation studies previously conducted in our laboratory using 14 C-radiolabeled CHX and liquid scintillation spectrometry demonstrated that D. acidovorans (WT15) cannot mineralize CHX (data not shown), although CHX degradation by several other bacterial species is known to occur (15).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Since these peaks were highly comparable with those of the CHX standard, we may further conclude that CHX does not appear to be modified or degraded within D. acidovorans biofilms. CHX degradation studies previously conducted in our laboratory using 14 C-radiolabeled CHX and liquid scintillation spectrometry demonstrated that D. acidovorans (WT15) cannot mineralize CHX (data not shown), although CHX degradation by several other bacterial species is known to occur (15).…”
mentioning
confidence: 87%
“…Some bacterial genera (i.e., Proteus and Providencia) may either be intrinsically resistant to CHX or have induced mechanisms of resistance due to phenotypic and genotypic changes (13). Penetration failure within biofilms, the permeability characteristics of the cellular outer membrane (14), CHX degradation (15), and the presence of resistance genes or plasmids have all been reported as possible causes for CHX resistance.…”
mentioning
confidence: 99%
“…4) To clarify the mechanisms of action on CH by this strain, we attempted to isolate the chlorhexidine products. [7][8][9] We concluded that CH was degraded via two pathways (one is a modified degradation pathway and the other is a direct degradation pathway) by Strain No. A-3.…”
Section: Introductionmentioning
confidence: 92%
“…A-3. 9) On the other hand, chlorhexidine aromatic degradation product (CHADP), CHADP-5 7) was a direct degradation compound of CH. To clarify the two degradation pathways of CH by this strain, we attempted to isolate the CHADPs from the culture filtrate.…”
Section: Introductionmentioning
confidence: 99%
“…Figura 2.13 -Estrutura molecular do CHDI-C, segundo Tanaka et al (2005) Os mesmos autores (Tanaka et al, 2006), realizando separação e análise de compostos semelhantes às descritas anteriormente, também sugerem a existência de mais dois compostos intermediários do mecanismo de degradação da CLX, 55 denominados CHADP-4 e CHADP-6. Eles seriam pares de degradação da PCU e PCA, respectivamente.…”
unclassified